17. Jahrestagung der Internationalen Kommission für die Fischerei im Nordwestatlantik (ICNAF) - Messtorff, J. (1967)
Johann Heinrich von Thunen-Institute, Federal Research Institute for Rural Areas, Forestry and Fisheries began publishing the Informationen aus der Fischereiforschung – Information on Fishery research in 2010